PENGARUH INOVASI PRODUK, INOVASI LAYANAN DAN ORIENTASI PASAR TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN MCDONALD’S DI KOTA SEMARANG) - Riyan Julianto; Widayanto Widayanto; Reni Shinta Dewi (Universitas Diponegoro, 2025)
Competition in the fast food restaurant industry in Indonesia is getting tighter. The hope is that McDonald's can be the top brand in fast food restaurants. However, based on data from the top brand index, McDonald's during 2020 - 2024 has always been in second place. In fact, the graph or index from 2022 - 2024 has decreased. This study aims to determine the effect of product innovation, service innovation and market orientation on purchasing decisions. The type of research used is explanatory research with 97 respondents. The sampling technique uses the purposive accidental sampling method. Data collection used physical questionnaires distributed at 9 McDonald's outlets in Semarang City. Data analyzed using SPSS Ver 25. The results of the study stated that product innovation, service innovation and market orientation have a positive effect on purchasing decisions of McDonald's consumers in Semarang City. The better the product innovation, service innovation and market orientation carried out, the more it increases consumer purchasing decisions. Product innovation helps meet changes in consumer preferences, service innovation improves consumer experience and market orientation makes it adaptive to market changes. McDonald’s can develop products with unique and different shapes to increase the novelty of the product. McDonald’s can improve the ease of use and reliability of Self Ordering Kiosk. McDonald’s needs to improve responsiveness to consumer input and complaints.